2005
DOI: 10.1104/pp.104.052423
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the RING-Type Ubiquitin Ligase Family of Arabidopsis   

Abstract: Approximately 5% of the Arabidopsis (Arabidopsis thaliana) proteome is predicted to be involved in the ubiquitination/26S proteasome pathway. The majority of these predicted proteins have identity to conserved domains found in E3 ligases, of which there are multiple types. The RING-type E3 is characterized by the presence of a cysteine-rich domain that coordinates two zinc atoms. Database searches followed by extensive manual curation identified 469 predicted Arabidopsis RING domaincontaining proteins. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
571
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 537 publications
(598 citation statements)
references
References 88 publications
21
571
1
5
Order By: Relevance
“…Moreover, the total number of N. benthamiana and Arabidopsis nuclei expressing MYB30-CFP is significantly reduced in the presence of MIEL1-YFPv, which rendered FRET-FLIM experiments a challenging task. Functional characterization of MIEL1 showed that this protein is an active E3 ligase able to ubiquitinate MYB30 and that, as previously described for other RING proteins, this activity depends on the integrity of key amino acids in the RING domain, which are essential for E2-dependent protein ubiqutination 8 . Finally, all these findings strongly suggest that epitope-tagging of the proteins does not affect their function.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Moreover, the total number of N. benthamiana and Arabidopsis nuclei expressing MYB30-CFP is significantly reduced in the presence of MIEL1-YFPv, which rendered FRET-FLIM experiments a challenging task. Functional characterization of MIEL1 showed that this protein is an active E3 ligase able to ubiquitinate MYB30 and that, as previously described for other RING proteins, this activity depends on the integrity of key amino acids in the RING domain, which are essential for E2-dependent protein ubiqutination 8 . Finally, all these findings strongly suggest that epitope-tagging of the proteins does not affect their function.…”
Section: Discussionsupporting
confidence: 60%
“…2, lane 3). Finally, an previously described active RING-type E3 ligase protein (At5g37270) 8 was not able to ubiquitinate MYB30 in vitro, further demonstrating the specificity of MIEL1-mediated ubiquitination of MYB30 ( Supplementary Fig. S4).…”
Section: Identification Of Miel1mentioning
confidence: 70%
See 2 more Smart Citations
“…Like SCF E3s, the RING-type E3 ligases serve as scaffolds to bring together the activated ubiquitin-E2 and the substrate in promoting the transfer of ubiquitin to the substrate. In contrast to that only few HECT-type E3s are identified in plants [32], the SCF and the RING-type E3 are found in hundreds of proteins [33,34]. The U-box is a novel E3 ubiquitin ligase activity-related protein domain that was first identified in the yeast ubiquitination factor UFD2 [35].…”
Section: Diversity Of Plant E3 Ligasesmentioning
confidence: 99%